The scope of student admissions by the Quotas Law: The case of the Federal University of Alfenas - Lopes, Ronaldo André; da Silva, Guilherme Henrique Gomes (Education Policy Analysis Archives, 2022)
In this paper, we highlight the scope of the Quotas Law at the Federal University of Alfenas in the period between 2014 and 2019. We analyzed the occupancy rate of vacancies and the racial profile of the freshmen in each year. We also carried out simulations on a scenario without the Quotas Law. Data consisted of information regarding enrollment of students through the Brazilian Unified Selection System. Data were analyzed by descriptive statistics and by an instrument that provided the percentage of students that would not enter in each program without the Quotas Law. Results highlight under-occupancy of the places addressed to Black and Indigenous students from public school system. This situation was more accentuated when was related to race and low income. Places addressed to students with disabilities were also under-occupied in the period. Still, the results show that the Quotas Law was responsible for racial diversity in this institution, since few Black students have entered the university through the broad competition category. Finally, the simulations showed that, in a scenario without the Quotas Law, students from the public school system would encounter greater obstacles to access this university, especially Black students. The most significant cut would be in programs in the biological sciences and health.